2012
DOI: 10.22237/jotm/1333238640
|View full text |Cite
|
Sign up to set email alerts
|

The role of returns management orientation, internal collaboration, and information support in reverse logistics

Abstract: While reverse logistics has gained significant interest in recent years, the research on its antecedents is still far from comprehensive. The current study utilizes data collected from China to empirically test a conceptual model that is developed based on the resource based view of the firm. It is proposed that returns management orientation, internal collaboration, and information support are important predictors of reverse logistics performance. The structural equation modeling analysis supports these propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For instance, machine learning can be used at a reverse vending machine to approximate when the bin is full, times of heavy usage at the bin, and use this information to ensure a good customer experience at the bin (Walk, Hirt, Kühl, & Hersløv, 2020, p. 113). All this is needed for effective decision making in RL, and lack of such will affect the efficiency of RL processes (Mai, Chen, & Anselmi, 2012; Srivastava, 2013). This would affect the customer experience.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, machine learning can be used at a reverse vending machine to approximate when the bin is full, times of heavy usage at the bin, and use this information to ensure a good customer experience at the bin (Walk, Hirt, Kühl, & Hersløv, 2020, p. 113). All this is needed for effective decision making in RL, and lack of such will affect the efficiency of RL processes (Mai, Chen, & Anselmi, 2012; Srivastava, 2013). This would affect the customer experience.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies analyze economic issues, environmental issues, market issues andproduct quality, among other issues. Additionally, the literature has shown that information technology (IT) resources are required for effective decision making in RL [17]. All of these activities require advanced IT systems.…”
Section: Introductionmentioning
confidence: 99%
“…In FL and RL, the resource-dependent theory (RDT) and RBV imply that collaboration between members of the SC can bring about better results (Moubed and Mehrjedi, 2014;Mai et al, 2012). RBV suggests that effective use of a firm's unique resources can lead to sustained competitive advantage.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%